On the decidability of boundedness problems for counter Minsky machines - E. V. Kuzmin; D. Ju. Chalyy (Моделирование и анализ информационных систем, 2008)
In the paper the decidability of boundedness problems for counter Minsky machines is investigated. It is proved, that for Minsky machines with two counters the boundedness is partial decidable, but for the total boundedness problem does not even exist a semidecision algorithm. On the other hand, for one-counter Minsky machines all these problems are polinomial (quantitatively of local machine states) decidable.